2018
DOI: 10.21608/adjg.2018.7995
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Nano-Hydroxyapatite as Dentin Desensitizer

Abstract: Objectives: This clinical study was conducted to evaluate the efficiency of nanohydroxyapatite (n-HAp) in reducing dentin hypersensitivity individually or combined with fluoride. Materials and methods: Forty hypersensitive teeth from 10 patients with hypersensitive symptoms were treated using hydroxyapatite nanoparticles (nHAp) gel at different concentrations/ sodium fluoride (NaF) containing according to four treatment groups: Group 1; 15% nHAp + 1% NaF, Group 2; 15% nHAp, Group 3; 25% nHAp+ 1% NaF, Group 4; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 17 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…A total of 7515 articles were excluded after reading titles and/or abstracts, 12 records were excluded since reports were not retrieved, 57 records from database registers and 18 identified through other methods were read and analyzed in their full-text, and 55 records were excluded for reasons such as not good drugs tested ( n = 34), in vitro studies ( n = 11), or study on tooth decay ( n = 10), as shown in Figure 1 . Twenty records met the inclusion criteria and were included in the systematic review: Poliakova et al, 2022 [ 30 ], Alharith et al, 2021 [ 31 ], Amaechi et al, 2021 [ 32 ], Eyuboglu et al, 2020 [ 33 ], Usai et al, 2019 [ 34 ], Amaechi et al, 2018 [ 35 ], Ameen et al, 2018 [ 36 ], Anand et al, 2018 [ 37 ], Vano et al, 2017 [ 38 ], De Oliveira et al, 2016 [ 39 ], Wang et al, 2016 [ 40 ], Gopinath et al, 2015 [ 41 ], Jena et al, 2015 [ 42 ], Mehta et al, 2015 [ 43 ], Naoum et al, 2015 [ 44 ], Mehta et al, 2014 [ 45 ], Porciani et al, 2014 [ 46 ], Vano et al, 2014 [ 47 ], Ghassemi et al, 2009 [ 48 ], and Geiger et al, 2003 [ 49 ]. The selection process has been detailed in the attached PRISMA flowchart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 7515 articles were excluded after reading titles and/or abstracts, 12 records were excluded since reports were not retrieved, 57 records from database registers and 18 identified through other methods were read and analyzed in their full-text, and 55 records were excluded for reasons such as not good drugs tested ( n = 34), in vitro studies ( n = 11), or study on tooth decay ( n = 10), as shown in Figure 1 . Twenty records met the inclusion criteria and were included in the systematic review: Poliakova et al, 2022 [ 30 ], Alharith et al, 2021 [ 31 ], Amaechi et al, 2021 [ 32 ], Eyuboglu et al, 2020 [ 33 ], Usai et al, 2019 [ 34 ], Amaechi et al, 2018 [ 35 ], Ameen et al, 2018 [ 36 ], Anand et al, 2018 [ 37 ], Vano et al, 2017 [ 38 ], De Oliveira et al, 2016 [ 39 ], Wang et al, 2016 [ 40 ], Gopinath et al, 2015 [ 41 ], Jena et al, 2015 [ 42 ], Mehta et al, 2015 [ 43 ], Naoum et al, 2015 [ 44 ], Mehta et al, 2014 [ 45 ], Porciani et al, 2014 [ 46 ], Vano et al, 2014 [ 47 ], Ghassemi et al, 2009 [ 48 ], and Geiger et al, 2003 [ 49 ]. The selection process has been detailed in the attached PRISMA flowchart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up range varied from immediately to 6 months. Most of the studies performed a 4-week follow-up phase [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therapeutic strategies to reduce the dentin hypersensitivity are from prescribing desensitizer agents at home in mild cases, treatment in office in cases of no improvement or in severe, root canal treatment in very severe cases not responding to any at home or in office methods that only one tooth shows symptoms [4]. Various desensitizer agents with different mechanisms such as ProArgin™ (arginine 8%) and novamin (calcium phosphosilicate 5%) [5], nanohydroxyapatite 25% [6], and concentrations of 5 to 10% potassium oxalate [7] have been used in the dentin hypersensitivity treatment. Fluoride varnish closes the dentinal tubules by forming a mechanical barrier.…”
Section: Introductionmentioning
confidence: 99%